Pembelajaran Berdiferensiasi: Analisis Literasi Kimia pada Materi Ikatan Kimia melalui Pendekatan Culturally Responsive Teaching Terintegrasi Etnokimia - Salma Fauzia Wardani; Sri Yamtinah; Bakti Mulyani; Endang Susilowati; Maria Ulfa; Mohammad Masykuri; Ari Syahidul Shidiq (Jurnal Penelitian Pendidikan IPA, 2024)
This study aims to obtain information and analyze the chemical literacy profile of class X students of one of public high school in Surakarta on chemical bonding material after carrying out differentiation learning with Culturally Responsive Teaching integrated with ethnochemistry. This research used descriptive qualitative approach with post-test only design. The research was conducted on 36 students of class X at one of public high school in Surakarta during 2 meetings. The results of the study showed that the literacy level of students after learning was carried out there were 25% of students classified as high, 56% classified as medium, and 19% classified as low. Based on the results of the analysis on each indicator of chemical literacy, students showed very good levels on all indicators, namely content, context, high-level learning skills, and affective. Therefore, the level of chemical literacy of students is classified as good after learning is differentiated with Culturally Responsive Teaching integrated with ethnochemistry because learning becomes contextual, meaningful, and in accordance with student learning readiness.